Characterization of Microbiota Metabolites Involved in the Gut-Brain Axis. - Alden, Nicholas. (Tufts University. Tisch Library., 2019)
The gut microbiota have been the subject of vigorous research in the last 20 years. Perturbation of normal microbial communities, in the gut have been linked with negative health outcomes including diabetes, obesity, and opportunistic pathogen infections such as Clostridium difficile. More recently, connections between these microorganisms and the host's brain have been proposed with implications in research on mental health and development. The route through which this communication is affected has not been fully elucidated. In this dissertation, I will describe our recent efforts to understand one possible route of communication between the microbiota and host: direct transport of microbial metabolites from the gut to the brain via the bloodstream. To accomplish this, we developed a novel workflow that applies biological context for the annotation of metabolites in untargeted liquid chromatography mass spectrometry metabolomics experiments. This workflow that we dubbed Biologically Consistent Annotation of Metabolomics Data, or BioCAn, outperforms existing metabolomics annotation tools by proposing more correct annotations for metabolites. Using this workflow, we profiled metabolites associated with the microbiota in the gut, blood, and brain of mice treated with an antibiotic cocktail to eliminate the bacteria in their gut. Through this approach, we confirmed existing studies that have linked the microbiota to carbohydrate metabolism and metabolism of plant secondary metabolites. In addition, we observed possible evidence of leucine biosynthesis by mouse microbiota which has not been previously described in the literature. Finally, we selected 4 metabolites that were significantly depleted or significantly accumulated in the gut of antibiotic treated mice indicating an association with the microbiota to test in an in vitro model of the blood-brain barrier (BBB). These metabolites were also detected in the serum and brain and are known participants in microbial metabolism. One of these metabolites, p-hydroxyphenyllactic acid (p-HPLA), was shown to be moderately permeable across the BBB compared to caffeine, a metabolite that is known to be highly permeable. These results suggest microbial-associated metabolites have the capacity to travel from the gut to the brain where they may affect function.; Thesis (Ph.D.)--Tufts University, 2019.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: Kyongbum Lee.; Committee: Arul Jayaraman, David Kaplan, and Nikhil Nair.; Keyword: Chemical engineering.